Perancangan Ulang UI/UX Website E-Learning UNMUL Menggunakan Metode Design Thinking - Aulia, Hadriani; Setyadi, Hario Jati; Jundillah, Muhammad Labib (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2024)
The rapid advancement of technology necessitates effective information systems in universities to enhance academic program quality. Mulawarman University addresses this through e-learning, yet users, especially students and lecturers, encounter challenges with the interface. This research aims to redesign the UNMUL e-learning website for better usability. Using the Design Thinking method, the study focuses on user issues and translates them into feature requirements. Data were collected through interviews and usability testing with students and lecturers. The findings reveal that the redesigned application supports various teaching and learning activities while reflecting Mulawarman University's identity. Usability testing showed high scores: 86 for the lecturer prototype and 80 for the student prototype. Additionally, the User Experience Questionnaire results are classified as excellent according to UEQ benchmarks.